Guest-induced reversible structural transitions and concomitant on/off luminescence switching of an Eu(III) metal-organic framework and its application in detecting picric acid - Li, Ao
We report a flexible metal-organic framework (MOF), (Me2NH2)(3)[ Eu-3(MHFDA)(4)(NO3)(4)(DMF)(2)]center dot 4H(2)O center dot 2MeCN (1) (H(2)MHFDA = 9-methyl-9-hydroxy-fluorene-2,7-dicarboxylic acid), which was synthesized by a hydrothermal method and structurally characterized. This MOF has a three-dimensional framework structure with one-dimensional rhombic channels and the framework can be reversibly transformed between two phases upon release/uptake of the guest molecules. The vacuum drying process is accompanied by the loss of luminescence of the MOF, while the luminescence is recovered upon resoaking in DMF. The potential of the material for PA sensing was studied in DMF through the luminescence quenching experiments, which elucidate that this material is a potential turn-off luminescent sensory material for the selective detection of PA.